DESAIN OPTIMAL LOAD FREQUENCY CONTROL (LFC) PADA SISTEM PEMBANGKIT LISTRIK TENAGA MIKROHIDRO (PLTMH) MENGGUNAKAN METODE PARTICLE SWARM OPTIMIZATION (PSO) - Tri Siswanto; Dwi Hendra Kusuma; Rukslin Rukslin; Agus Raikhani (SENTIA 2016, 2016)
Micro-hydro system currently chosen because it has advantages economically, technically, and environmentally friendly. Micro-hydro is suitable for use in areas difficult to reach grid. Problems often occur at the micro hydro is not constant generator rotation caused by load changes. Thus causing frequency fluctuations in the system that could result in damage electrical equipment. Therefore in this study covered a frequency controller based PID controller to regulate Load Frequency Control (FLC). To obtain the optimal parameters PID controller then used several methods for comparison. Among the methods of control, with standard PID controller, with conventional PID Ziegler-Nichols, with PID Auto tuning Matlab and with PID be tuned method Particle Swarm Optimization (PSO). Micro hydro power plant systems in this study using an induction generator, a servo motor operated as governor, and several components. Its be Modeled in simulation using Matlab-Simulink program. The simulation results showed that the application of tuning PID-PSO can speed up the settling time frequency response and improve the response overshoot.